Respiratory Epithelial Adenomatoid Hamartoma: A Very Rare Entity Originating from the External Auditory Canal - Shokouhi, Behrouz (Iran J Pathol, 2020)
Respiratory epithelial adenomatoid hamartoma (REAH) is an uncommon lesion of the upper aerodigestive tract. It is characterized by abnormal glandular formations with ciliated epithelium arising from the nasal cavity, paranasal sinuses and nasopharynx, but other locations have also been described. We did not find any other cases of this hamartomas in the external auditory canal in the literature. A 40-year-old man was referred to the otorhinolaryngology department due to otorrhea and decreased hearing from 1 year ago. Otoscopic examination showed a reddish hemorrhagic mass in the left external auditory canal. Intraoperatively, the tumor was completely resected. The pathologic findings were consistent with REAH.